(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
This study aim at investigating the tolerance of two tomato rootstock (Sprit and ES-30502) widely speared in Syria and used for crafting some tomato hybrids grown in green houses for different salinity levels (0- 25- 50- 75- 100- 150 mM NaCl). The results show that the germination of rootstock Sprit seeds was not influenced by high salinity 150 mM despite a delay of 1-2 days compared with the control. A reduction of 15% was observed in the rootstock ES-30502 at 100 and 150 mM NaCl salinity levels, in addition to slower percentage rate of germination. In contrast, the effect of salinity on the development of the radical and rootlet was more pronounced in Sprit compared to ES-30502. Salinity decreased the growth of both shoots and roots, and also decreased nutrient acquisition in both rootstocks, but to a lesser degree in ES-30502. The uptake of K was not greatly affected and concentrations in shoot remained normal. The concentrations of Ca and Mg were also not affected by salinity. The most pronounced effect of salinity was on nitrogen effect (NO3) which was reduced greatly in both rootstocks. This was accompanied by accumulation of free NO3 ions in the shoot tissue (58 and 45 % of total N uptake at salinity level of 150 mM). It is most likely that toxicity of Na and Cl ions, and consequent osmotic changes in cell tissue led to slower nitrate reductase activity (NRA) and accumulation of NO3. يهدف البحث إلى دراسة تحمل أصلين من البندورة (Sprit ، و ES-30502) ينتشران في سورية، بوصفهما أصولاً لتطعيم الهجن المزروعة في البيوت المحمية، وذلك باستخدام تراكيز متدرجة من NaCl (0 – 25- 50- 75- 100- 150 ميليمول). أظهرت نتائج الدراسة أن إنبات بذور الأصل Sprit لم تتأثر بالملوحة حتى في التركيز المرتفع من الملوحة 150 ميليمول، رغم تأخر الإنبات من 1-2 يوماً مقارنة بالشاهد، بينما انخفض معدل الإنبات بمعدل 15 % في الأصل ES-30502، وتأثرت، أيضاً، وتيرة الإنبات في مستويي الملوحة 100 و 150 ميليمول. على العكس من ذلك فقد كانت تأثيرات الملوحة أكثر سلبية في تطور البادرات من حيث نمو الريشة، والجذير للأصل Sprit مقارنة بالأصل ES-30502 . أدت الملوحة أيضاً إلى انخفاض نمو كل من المجموعين الخضري والجذري، وامتصاص العناصر الغذائية لكلا الصنفين، لكن شدة تأثير الملوحة كانت أقل وضوحاً في الأصل ES-30502 مقارنة بالأصل Sprit. لم يتأثر بشكل كبير امتصاص البوتاسيوم، وبقيت تراكيزه في المجموع الخضري جيدة، في حين لا تأثير يذكر للملوحة في تراكيز الـ Ca و الـ Mg . كان التأثير الأبرز في امتصاص النترات التي انخفضت بشكل عام، وتراكمت في المجموع الخضري بصورتها الحرة (58 و 45% من مجموع الآزوت الكلي الممتص عند مستوى الملوحة 150 ميليمول NaCl). ربما يكون تراكم النترات نتيجة لتباطؤ عمل أنزيم إرجاع النترات بسبب سمية شاردتي الـ Na والـ Cl في الأنسجة النباتية، وتغيرات الضغط الأسموزي في الأنسجة الخلوية.